KAJIAN KRITIK SANAD DAN MATAN HADIS TENTANG PERINTAH SHALAT TERHADAP ANAK - Muhsin, Muhsin (Musawa: Journal for Gender Studies, 2018)
Prayer is one of the pillars of Islam, therefore the importance of the command of the Prayer from the beginning applied by the Prophet has its own wisdom. In this case, this writer wants to study the hadith of the Prophet Muhammad about the command of prayer. Using the Takhrij Hadith method, the hadith can be known whether he belongs to the Shohih Hadith or the Dhaif Hadith. This is very important because the hadith of the Prophet Muhammad is the second source of law in Islam, of course this is very influential in Islamic law. Therefore this paper aims to clarify the status of a hadith which explains the command of prayer for children. ` Takhrij hadith the author will use the dictionary Takhrij hadith namely Kitab Mu'jam al-Mufahraz. After each of the narrators will be examined one by one, so that the hadith to be studied can be traced whether this hadith is dhaif or Shahih If the results are shohih, then it will give confidence that educating children from a small age, especially prayer, is the guidance of the true Prophet. If the hadith is of value, then the hadith can still be used to motivate children about the prayer service. The reason for writing this article is because there are so many who doubt the credibility of a hadith that causing hadith to be one of the "soft" debates to lead to Islamic credibility, one of which is Ignaz Goldziher who doubts the Tafsir traditions. Therefore the takhrij method wants to prove that the hadith about the command of prayer is the hadith of Shohih or the hadith of Dhaif. In a review of the literature this research has been conducted in various online libraries, the author gets four research titles, namely three of them thesis and one writing in a journal. The research is Padjrin dengan judul â€œPola Asuk Anak dalam Perspektif Pendidikan Islam â€ dalam jurnal Intelektualita Vol. 5 No. 1 tahun 2015, dan Rizka Hendariah Skripsi UIN Syarif Hidayatullah Jakarta Fakultas Tarbiyyah dan Ilmu Keguruan dengan judul â€œKonsep Pendidikan Anak Dalam Keluarga (Mendidik Anak Tanpa Kekerasan) dan Jihan Avie Yusrina dengan judul skripsi â€œStudi Analisis Hadis Tentang Perintah Shalat Pada Anak Sejak Usia Tujuh Tahun Dalam Perspektif Pendidikan Islam. Unayah, Peranan Keluarga Dalam Pembiasaan Ibadah Shalat Anak Usia 7-10 Tahun â€œStudi Kasus di Lingkungan RT 07/01 Jakarta Utara Clincingâ€ .